선택실험법을 적용한 습지보호지역의 문화서비스 가치 추정 - 김남희; Namhee Kim; 오치옥; Chi-ok Oh; 안소은; Soeun Ahn (환경정책, 2023)
이 연구에서는 습지보호지역의 문화서비스를 관광·휴양, 경관·심미, 교육서비스로 세분화하여 경제적 가치를 추정하고, 주 방문객인 거주민과 관광객이 평가하는 문화서비스 가치 차이를 확인하고자 하였다. 연구를 위해 선택실험법을 이용하였으며, 대표 습지보호지역인 창녕 우포늪의 방문객을 대상으로 설문조사를 시행하여 총 245명의 자료를 수집하였다. 연구 결과, 습지보호지역이 제공하는 문화서비스의 총 가치는 1인당 연간 14,357원으로 도출되었으며, 그 중 관광·휴양적 가치가 가장 높게 나타났다. 또한, 주요 방문객 중 거주민은 21,458원, 관광객은 13,778원으로 문화서비스 가치를 평가하여 거주민의 지불의 사액이 관광객보다 더 높게 나타났다. 이러한 차이는 자연과의 접촉, 생태적 가치관, 환경 규범, 그리고 장소성의 차이에서 기인한 것으로 추측된다. 이러한 연구 결과는 습지보호지역의 중요성 인식 향상을 위해 교육과 홍보 활동이 필요하다는 점을 시사한다. This study assessed the tourism and recreation, landscape/aesthetic, and educational values of cultural ecosystem services (CES). It also examined differences in the values of CES between tourists and residents. We collected a total of 245 questionnaires from visitors to the Upo wetland protected area using choice experiments as a valuation method. The results revealed that the CES values of visitors were approximately 14,360 KRW, with the tourism/recreation value being the highest. The CES values of residents were approximately 21,460 KRW, while those of tourists were 13,780 KRW. Furthermore, the difference in CES values probably resulted from factors such as individuals’ contact with nature, ecological views, subjective norms, and sense of place. The results indicate that public education and outreach activities will be required to raise their awareness of the importance of wetland protected areas.